1999
DOI: 10.4098/at.arch.99-1
|View full text |Cite
|
Sign up to set email alerts
|

Habitat and food preferences in a guild of insectivorous mammals in the Western Pyrenees

Abstract: Habitat and food preferences in a guild of insectivorous mammals in the Western Pyrenees Enrique CASTIEN and Joaquim GOSALBEZ Castien E. and Gosälbez J. 1999. Habitat and food preferences in a guild of insectivorous mammals in the Western Pyrenees. Acta Theriologica 44: 1-13.The use of trophic and spatial resources in a guild composed of five species of insectivorous mammals (Galemys pyrenaicus, Talpa europaea, Neomys fodiens, Sorex coronatus, and Sorex minutus) was studied. The characteristics of the macrohab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
23
4
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 32 publications
7
23
4
1
Order By: Relevance
“…This study also provides unprecedented insights into the summer trophic niche of N. fodiens, by identifying prey identity at the family and genus levels for the first time (but see at the order level: Castién and Gosálbez, 1999;Churchfield, 1985;Churchfield and Rychlik, 2006). In accordance with previous studies conducted at a higher taxonomic level, we found that N. fodiens fed on terrestrial prey at a larger extent than G. pyrenaicus, with a dominance of terrestrial Diplopoda and Insecta in its diet.…”
Section: Novel Insights Into the Diet Of G Pyrenaicus And N Fodienssupporting
confidence: 88%
See 3 more Smart Citations
“…This study also provides unprecedented insights into the summer trophic niche of N. fodiens, by identifying prey identity at the family and genus levels for the first time (but see at the order level: Castién and Gosálbez, 1999;Churchfield, 1985;Churchfield and Rychlik, 2006). In accordance with previous studies conducted at a higher taxonomic level, we found that N. fodiens fed on terrestrial prey at a larger extent than G. pyrenaicus, with a dominance of terrestrial Diplopoda and Insecta in its diet.…”
Section: Novel Insights Into the Diet Of G Pyrenaicus And N Fodienssupporting
confidence: 88%
“…Several aquatic or semi-aquatic animals are known to prey and use similar food and habitat resources as G. pyrenaicus and act as potential competitors for resource acquisition: the brown trout Salmo trutta and the dipper Cinclus cinclus (Bertrand, 1994;Santamarina, 1993;Santamarina and Guitian, 1988), the Eurasian water shrew Neomys fodiens (Castién and Gosálbez 1999;Morueta-Holme et al, 2010;Santamarina and Guitian 1988), the Mediterranean water shrew Neomys anomalus (Santamarina, 1993) and the Pyrenean brook newt Calotriton asper (Bertrand, 1994). Among these species N. fodiens exhibits similar habitat preferences as G. pyrenaicus, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, small mammals are important in grassland food 80 webs, both as consumers or top-down regulators of vegetation and arthropods (e.g. most shrews are 81 insectivores), and as a food resource for reptiles, birds and mammals (Castién and Gonsálbez, 1999;82 Mohammadi, 2010; Torre et al, 2007;Vieira et al, 2009 (Gerla et al, 2012). The impact of grassland restoration on small 87 mammals has been addressed in a handful of studies in North America.…”
mentioning
confidence: 99%